Las relaciones internacionales regionales de Chile hacia 1904 - Tapia Figueroa, Claudio (Claudio Andres), 1972-; Garay Vera, Cristián (Book collections on Project MUSE., 2021)
This work, the result of initiatives that brings together several universities and specialists in the country, appears when a century has passed since the emergence of the history of international relations as a historical sub-discipline. For this reason, it has seemed relevant to us to signify this commemoration by addressing a theme that has its roots in the field of studies mentioned. Indeed, much has been written about the 1904 Treaty, both in Chile and Bolivia, hence we already see a series of recent studies that have clarified this process. For this reason, this book does not deal with the agreement itself, but with its relevance as a milestone in a decisive change in Chile's trajectory as the winner of the War of the Pacific, until 1929.